Mitochondria Related Cell Death Modalities and Disease - Tian, Chuwen; Liu, Yifan; Li, Zhuoshu; Zhu, Ping; Zhao, Mingyi (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are well known as the centre of energy metabolism in eukaryotic cells. However, they can not only generate ATP through the tricarboxylic acid cycle and oxidative phosphorylation but also control the mode of cell death through various mechanisms, especially regulated cell death (RCD), such as apoptosis, mitophagy, NETosis, pyroptosis, necroptosis, entosis, parthanatos, ferroptosis, alkaliptosis, autosis, clockophagy and oxeiptosis. These mitochondria-associated modes of cell death can lead to a variety of diseases. During cell growth, these modes of cell death are programmed, meaning that they can be induced or predicted. Mitochondria-based treatments have been shown to be effective in many trials. Therefore, mitochondria have great potential for the treatment of many diseases. In this review, we discuss how mitochondria are involved in modes of cell death, as well as basic research and the latest clinical progress in related fields. We also detail a variety of organ system diseases related to mitochondria, including nervous system diseases, cardiovascular diseases, digestive system diseases, respiratory diseases, endocrine diseases, urinary system diseases and cancer. We highlight the role that mitochondria play in these diseases and suggest possible therapeutic directions as well as pressing issues that need to be addressed today. Because of the key role of mitochondria in cell death, a comprehensive understanding of mitochondria can help provide more effective strategies for clinical treatment.